2009
DOI: 10.1136/hrt.2008.161653
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler velocity is superior to strain imaging in predicting long-term cardiovascular events after cardiac resynchronisation therapy

Abstract: Echocardiographic evidence of prepacing systolic dyssynchrony measured by TDI velocity, but not TDI strain, predicted lower long-term cardiovascular events after CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Parameters that have recently been studied to improve patient selection include QRS morphology in MADIT-CRT (left bundle branch block (LBBB), rather than non-LBBB, patterns appears to be the predominant morphology-that is, related to response), 100 baseline LV radial dyssynchrony, discordant LV lead position, and myocardial scar in the region of the LV pacing lead, 101 and prepacing systolic dyssynchrony measured by tissue Doppler imaging velocity. 102 Consistent with existing knowledge, LV lead positioning has been reconfirmed to be important in MADIT-CRT patients 103 and patients with non-ischaemic dilated cardiomyopathy. 104 The prospective, randomised SMART-AV (SmartDelay determined AV optimisation: a comparison with other AV delay methods used in CRT) study compared three different methods of AV optimisation (fixed empirical AV delay of 120 ms, echo-optimised AV delay, or AV optimisation with an ECG-based algorithm) in 980 patients with a CRT device to determine if any method was superior.…”
Section: Cardiac Resynchronisation Therapy and Pacingsupporting
confidence: 58%
“…Parameters that have recently been studied to improve patient selection include QRS morphology in MADIT-CRT (left bundle branch block (LBBB), rather than non-LBBB, patterns appears to be the predominant morphology-that is, related to response), 100 baseline LV radial dyssynchrony, discordant LV lead position, and myocardial scar in the region of the LV pacing lead, 101 and prepacing systolic dyssynchrony measured by tissue Doppler imaging velocity. 102 Consistent with existing knowledge, LV lead positioning has been reconfirmed to be important in MADIT-CRT patients 103 and patients with non-ischaemic dilated cardiomyopathy. 104 The prospective, randomised SMART-AV (SmartDelay determined AV optimisation: a comparison with other AV delay methods used in CRT) study compared three different methods of AV optimisation (fixed empirical AV delay of 120 ms, echo-optimised AV delay, or AV optimisation with an ECG-based algorithm) in 980 patients with a CRT device to determine if any method was superior.…”
Section: Cardiac Resynchronisation Therapy and Pacingsupporting
confidence: 58%
“…LV dyssynchrony at baseline was an independent determinant of cardiovascular mortality (hazard ratio 0.463, 95% confidence interval 0.720 to 0.972; Pϭ0.005). 36 Leyva et al 60 demonstrated the prognostic value of LV mechanical dyssynchrony assessed with MRI. In 148 heart failure patients, LV mechanical dyssynchrony was measured as the temporal dispersion of peak inward myocardial motion throughout the cardiac cycle.…”
Section: Mechanical Dyssynchrony and Crt: Focus On Predicting Longmentioning
confidence: 99%
“…The majority of the TDI-derived dyssynchrony indices are based on differences in time to onset or time to peak systolic velocity between 2, 4, or more opposing LV walls. 11,12,35,36 For example, the measurement of the maximum peak systolic velocity time delay between 4 opposing walls yielded a cutoff value of 65 ms to indicate the presence of significant LV dyssynchrony. 11 This TDI-derived LV dyssynchrony parameter yielded a sensitivity and specificity of 92% to predict significant LV reverse remodeling after CRT.…”
Section: Initial Echocardiographic Approaches To Predict Crt Responsementioning
confidence: 99%
“…Intraventricular dyssynchrony as evidenced by cardiac magnetic resonance also predicts mortality and morbidity after CRT 6. Furthermore, mechanical dyssynchrony, either independently or in combination with other clinical parameters, is associated with a superior survival outcome after CRT 8 9. Intuitively, therefore, the key benefit of CRT in restoring left ventricular synchrony should also extend to this group of narrow QRS patients, in an attempt to avert progressive dilation and electrical remodelling and possibly to translate into better long-term survival and a reduction in hospitalisations due to heart failure.…”
mentioning
confidence: 99%